Places - Real and Imagined - in the Letter to Philemon - Tolmie, D. F. (Neotestamentica, 2025)
This contribution explores three aspects of the reception history of the Letter to Philemon to highlight the diverse ways in which interpreters have envisioned the spaces presupposed by or mentioned in the letter, as well as the significant impact of certain preconceptions and assumptions on their understanding of these spaces. First, the three options proposed by scholars for the location of Paul’s imprisonment (Rome, Caesarea, or Ephesus) are discussed, along with the reasons provided by them for favouring each choice. Secondly, the different views of the type of imprisonment Paul experienced are reviewed, including the arguments scholars offer for their preferences. Thirdly, the different interpretations of the term ξɛνία (translated as "accommodation" or "guest room") mentioned in verse 22 are investigated. Finally, the concluding section offers suggestions on how best to address the challenges posed by these three interpretive issues, but the inherent difficulty of proving any specific choice with certainty is also highlighted.